The In Silico Toxicity of Serai Wangi (Cymbopogon nardus) and Mimba (Azadirachta indica - anggraeni, Henny endah; Purwono, Rini Madyastuti; Sutardi, Lina Noviyanti; Mustika, Aulia Andi; Manalu, Wasmen; Andriyanto, Andriyanto (Acta VETERINARIA Indonesiana, 2025)
Natural active-ingredient-based shampoos offer an effective and eco-friendly solution for maintaining the skin and hair health of companion animals. This study aimed to predict the toxicity of phytochemical compounds from citronella oil (Cymbopogon nardus) and neem oil (Azadirachta indica) using an in silico approach with the ProTox-II platform. The analyzed compounds included limonene, farnesene, eucalyptol, menthol, oleic acid, p-cymene, indole, (9Z)-9- octadecenamide, amylbenzene, p-cresol, camphor, and dieugenol, selected based on LC-MS/MS analysis. The evaluated toxicological parameters comprised oral acute toxicity (LD50), hepatotoxicity, immunotoxicity, genotoxicity (cytotoxicity, mutagenicity, carcinogenicity), as well as nuclear receptor signaling and stress response pathways. The results revealed that p-cymene exhibited the highest toxicity (LD50 = 3 mg/kg, class I), followed by oleic acid (LD50 = 48 mg/kg, class II), whereas amylbenzene was classified as non-toxic (LD50 = 6430 mg/kg, class VI). All compounds were predicted to be non-hepatotoxic and non-immunotoxic; however, p-cymene, indole, and amylbenzene showed potential carcinogenicity. Limonene was predicted to be active against AhR, ER, MMP, and ATAD5 receptors, while dieugenol was active against nrf2/ARE, HSE, and MMP. These predictions suggest that most compounds are safe for shampoo applications, except for p-cymene, which requires further evaluation. This study provides preliminary insights for the development of safe and effective natural-based shampoos.